Dial c for chihuahua ebook - Curtis, Waverly (A Barking Detective Mystery, 2011)
Pepe, aka el Jefe, the talking Chihuahua, helps his new owner, PI Geri Sullivan, nab her first killer in the debut Barking Detective Mystery. Pepe may have soft white fur, big brown eyes, and macho attitude—but he's no furry fashion fad. Pepe can talk—even if his new owner, Geri Sullivan, seems to be the only person who can understand him. When Geri takes her first assignment for a quirky private investigator named Jimmy G and stumbles over a Seattle millionaire's corpse, Pepe proves to be worth his weight in liver treats. Suspicion falls on the not-so-grieving widow who wants to finance a reality TV show, Dancing with Dogs. Normally, Pepe wouldn't be caught muerte in a sparkly costume. However, he has to sniff out the real killer and keep Geri safe. Lesser dogs might flinch. But Pepe isn't the kind to turn tail and run . . . "Pepe is a delight!" — RT Book Reviews, 4 stars